Patient controlled analgesia and respiratory depression [Hasta kontrollü analjezi yóntemi ve solunum depresyonu] - (:unkn) unknown (My University, 2003)
Postoperative patient controlled analgesia is a popular analgesic technique providing more effective analgesia than traditional on-demand administration. However occasional patients receiving opioids in this manner develop severe respiratory depression. The incidence and the risk factors for respiratory depression during patient controlled analgesia are discussed in this paper.
Keywords: Patient controlled analgesia; Respiratory depression